STRUKTUR KOMUNITAS IKAN PADA SUNGAI AIR REMUDING KECAMATAN RIAU SILIP KABUPATEN BANGKA - Hodri Hodri; Andi Gustomi; Eva Utami (Akuatik: Jurnal Sumberdaya Perairan, 2020)
Air Remuding River is a river which located in Pangkal Niur Lama Hamlet, Riau Silip District, Bangka Regency. Air Remuding River is ± 1 km from Pangkal Niur Lama Hamlet. This study aims to analyze the structure of the fish community in the Air Remuding River and to analyze the relationship between the physical and chemical factors of the waters to the species composition of the fish in the Air Remuding River. This research conducted in the month of January 2020 in the waters of the Air Remuding River, Pangkal Niur Lama Hamlet, Riau Silip District, Bangka Belitung Islands Province. The results of this study indicate that the most common fish caught in the Air Remuding river we're 2501 fishes (Rasbora bankanensis). Diversity Index (H '), Air Remuding River fish with a range of 0.66-0.72. included in the criteria of moderate diversity, while the Uniformity Index (E), Air Remuding River fish were high uniformity and the Dominance Index ranged from 0.19 to 0.23. The composition of fish species in the Air Remuding River correlates with DO, depth, current velocity and nitrate.